Affordability and the Return on Investment of College Completion: Unique Challenges and Opportunities for Adult Learners. Issue 3 (1st September 2016) - Bowers, Amanda; Bergman, Matt
Abstract: It is increasingly understood that in order to be successful in today's economy a postsecondary degree is needed (National College Access Network, 2012 ). Approximately 65% of jobs in 2020 will require some form of postsecondary education (Carnevale, Smith, & Strohl, 2013 ), and of the 30 fastest growing occupations, more than half require postsecondary education (Bureau of Labor Statistics, 2013 ). There is good reason to focus on adult students: The United States will not meet projected workforce needs without educating more of its adult population. Data also show that the average earnings of young adults with a bachelor's degree are twice as high as that of workers with only a high school diploma, and adults with solely a high school diploma are just over twice as likely to be unemployed than their college-educated peers. These statistics point to the need for some form of education after high school, yet many adult learners are still choosing not to enroll or complete a degree, a trend that requires closer examination. In this article we review the current context in which adult learners are situated and discuss recommendations for research and practice.